Health-seeking behaviour and patient-related factors associated with the time to TB treatment initiation in four African countries: a cross-sectional survey - Andrea Rachow; Salome Charalambous; Katherine Fielding; Olena Ivanova; Olumuyiwa Owolabi; Violet Chihota; Denise Evans; Julieth Lalashowi; Kavindhran Velen; Pedroso Nhassengo; Farzana Sathar; Mohammed S Rassool (BMJ Publishing Group, 2024)
Introduction In 2022, tuberculosis (TB) was the second-leading cause of global deaths from a single infectious agent. Delays in initiating TB treatment can lead to increased morbidity and mortality. We describe the total delay in treatment initiation, identify patient-related factors associated with time to treatment initiation and explore health-seeking behaviour prior to treatment initiation among people living with TB (PLTB) in four African countries.Methods Cross-sectional survey nested in a large prospective cohort of adults (≥18 years) with drug-susceptible pulmonary TB. PLTB enrolled in South Africa, Tanzania, Mozambique and The Gambia between September 2017 and January 2020. Structured questionnaires were used to collect data on demographics and map the patient experience prior to treatment initiation. Total delay (weeks) was the time between the onset of the first TB symptom and the initiation of treatment at the health facility. We developed a Cox regression model to study the relationship between explanatory variables and the time-to-event outcome, TB treatment initiation.Results We enrolled 1400 participants (South Africa: 344, Tanzania: 282, Mozambique: 407, The Gambia: 367) (mean age 36 years, 66% male). Overall HIV prevalence was 42% but varied by country (South Africa: 68%, Tanzania: 49%, Mozambique: 45%, The Gambia: 7%). The overall median total delay was 6 weeks (IQR 4-10). People living with HIV (vs HIV negative; adjusted HR (aHR)=1.33 (95% CI 1.2 to 1.5)) and those living with a partner (vs married; aHR=1.35 (95% CI 1.1 to 1.6)) or single (vs married; aHR=1.24 (95% CI 1.1 to 1.4)) had a higher chance of initiating TB treatment. Primary care facilities and pharmacies were the main providers where individuals first sought care after experiencing TB symptoms.Conclusion There are delays in TB treatment initiation among presumptive TB individuals. Partnerships with pharmacies, active case finding and decentralised TB services may be important to incorporate into the National TB Control Programme.